The Effect of Padlet Application towards Students’ Narrative Writing at the Tenth Grade of SMAN 1 Malingping Lebak Banten in Academic Year 2023/2024 - Parida, Ida; Novari, Ari Fajria; Rohimajaya, Nur Azmi (Journal of Contemporary Issues in Primary Education, 2024)
This research paper aims to know whether there is a significant effect of Padlet application towards students’ narrative writing at the Tenth Grade of SMAN 1 Malingping Lebak-Banten In Academic Year 2023/2024. The authors paper used quantitative approach and quasiexperimental design. The technique in choosing the sample is cluster random sampling; the authors used XE 7 (36 students) as class experiment and XE 10 (36 students) as class control. The experimental group was taught narrative text in writing activity used Padlet application, where as the control group was taught used Google classroom. At the first meeting of the research, the researcher gave a pre-test to both the experimental group and the control group to measure the extent of students’ narrative writing. Then gave treatment for five meetings and the last meeting of the research, the researcher gave a post-test to find out the final results and to prove the significant effect after being given treatment using a Padlet application in the experimental group. In analyzing the data, the author used independent sample t-test by SPSS 29 for windows showed the value of t calculated> t- table was 25.100 in experimental class. And its significance value because less than 0.05 (P = 0.00 < 0.05 in experimental class). It can be concluded that the alternative hypothesis (Ha) was accepted. Therefore, the researcher concluded that the Padlet application has a good effect on Students’ Narrative Writing. In addition, this Padlet application is not only effectively used in learning writing but could also be used as an online learning medium because this Padlet application has space to communicate freely between teachers and students as well as between other students.